PENERAPAN SIKLUS BELAJAR UNTUK MENINGKATKAN KETERAMPILAN PROSES BELAJAR IPA SISWA KELAS 9H DI SMPN 10 JEMBER TAHUN 2019/2020 - Soesy Sri Wulandari; Suwoto Suwoto (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2021)
Abstract: This study aims to find out the improvement of IPA process skills through the 7E Learning Cycle on dynamic electrical materials in class 9H in SMP Negeri 10 Jember. This research was conducted at SMPN 10 Jember Jember. The instruments used in this study are IPA process skills observation sheet, learning cycle learning model implementation instrument (The 7 E LCM), test set and documentation. The research subjects were 9H class students as many as 32 students. The collected data is described and analyzed and then reduced and checked its validity using the triangulation method. The results of the analysis are obtained from the answers on the observation sheet. Overall, the 7E cycle model can improve IPA process skills in 9H class. Keywords: Process Skills, Dynamic Electricity, 7E Learning Cycle